A comparative study of static and dynamic properties of honeycomb non-pneumatic wheels and a pneumatic wheel. (December 2021) - Zheng, Zhou; Rakheja, Subhash; Sedaghati, Ramin
Three-dimensional finite element (FE) models of the honeycomb NPWs with three different spokes' configurations, realized by varying the cell angle, were formulated. The validity of the proposed NPW FE models was demonstrated by comparing the predicted wheel responses with the reported data. A FE model of the pneumatic wheel of identical size was also formulated and verified on the basis of the measured vertical force-deflection and cornering properties. The verified NPW models were subsequently employed to study their feasibility through comparisons of in-plane as well as out-of-plane properties with those of the pneumatic wheel. The influences of the cell angle and normal wheel load on the static and dynamic properties of the NPWs were also investigated. The results showed load-dependent longitudinal stiffness of the wheel due to strong coupling between radial and longitudinal deformations of the honeycomb spokes. The lateral stiffness, however, was observed to be load-independent due to negligible coupling between radial and lateral deformations of the spokes. The spokes of the honeycomb NPWs could thus be easily tuned to achieve vertical and longitudinal stiffness comparable to those of the reference pneumatic wheel. The lateral and cornering stiffness of the NPWs with the planar spokes, however, were substantially higher, irrespective of the spokes' configuration considered. The significantly higher cornering stiffness resulted in rapid saturation of the cornering force of the NPWs at side-slip angles about 1.1°, which is likely to cause lateral sliding of the wheels and potential loss of directional control under higher side slip conditions.